2014
DOI: 10.1111/jocs.12479
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Paraganglioma

Abstract: Cardiac paragangliomas are rare tumors arising from chromaffin cells. Two patients with cardiac paragangliomas underwent surgical resection with no evidence of recurrence three and 13 years following surgery. This report describes these two patients with cardiac paragangliomas and discusses their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional 2.5% mortality was reported for the immediate postoperative course. A review of individual case reports from 2014-2016, two years since Wang et al's review, shows no intraoperative mortality reported from 11 cases (12,18,19,(22)(23)(24)(25)(26)(27). Among these cases, one instance of intraoperative cardiac arrest occurred due to severe hemorrhage and one unexpected intraoperative circulatory collapse, however both ended with successful outcomes (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…After recovery from surgery, benign cardiac PGs that are completely resected with negative margins have been associated with favorable outcomes in survival with low rates of tumor recurrence (18,26). For those surviving the immediate post-operative course, a 1-year survival of 98.2% and 5-year survival of 78.2% has been reported (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recommend contrast-enhanced CT chest, abdomen and pelvis, cardiac MRI, and MIBG scan. [ 6 ] Further, Tomasian et al . report on the potential power of a combination of cardiovascular magnetic resonance with various image acquisition sequences in multiple orientations and PET-CT studies.…”
Section: Discussionmentioning
confidence: 99%
“…Non-Malignant Cardiac Tumors DOI: http://dx.doi.org /10.5772/intechopen.86944 reports or small series from large institutions. These masses include teratomas, hamartomas, fibromas, hemangiomas, paragangliomas, and mesotheliomas of the atrioventricular node [50,51]. Management is often similar to other cardiac masses and based on presenting symptoms, concern for embolic risk or obstructive physiology, and clinical risk of surgical intervention [52].…”
Section: Note: the Surgical Specimen Is From The Same Patient As The mentioning
confidence: 99%